Changes in Peristomal Skin Condition and User Experience of a Novel Ostomy Barrier Ring With Assisted Flow: A 6-Week Feasibility Study. Issue 5 (September 2018) - Hunt, Rhona; Kelleher, Kevin; Coffey, J. Calvin; Clarke Moloney, Mary; Ahern, Mary; Conway, Elaine; Hannigan, Ailish; Erwin-Toth, Paula; O'Sullivan, Leonard W.
Abstract : PURPOSE: This purpose of this study was to evaluate a novel barrier ring with an assisted flow mechanism by assessing changes in peristomal moisture-associated skin damage (MASD) and perceptions of comfort, security, handling, and discretion in persons with an ileostomy for 6 months or longer. DESIGN: Single-arm, open-labeled feasibility study. SUBJECTS AND SETTINGS: Twenty participants (aged ≥18 years) with an ileostomy for 6 months or more participated in the study and 12 completed data collection. The primary reason for dropouts concerned compatibility issues with the barrier ring when used with certain convex pouching systems. METHODS: Participants used the barrier ring along with their normal ostomy pouching system for a period of 6 weeks. Changes in skin condition were assessed using the Ostomy Skin Tool (OST). Participants' perception of the barrier rings' comfort, security, handling, and discretion were also recorded on a 10-point scale, where participants would offer a low score if their experience was negative and a higher score if their experience was positive. Participants changed pouches and barrier rings at their own discretion. For participants who completed the study, the average skin condition and median ratings of comfort, security, handling, and discretion at 6 weeks were compared to baseline values. RESULTS: Twelve of the 20 participants (60%) completed the study. For those who completed, the mean score on the OST decreased from 6.2 ± 1.90 (mean ± SD) at baseline to 3.4 ±1.73 at 6 weeks, indicating a mean reduction of 2.8 (95% CI, −1.6 to −3.9; P < .001). The peristomal skin condition of 9 participants improved, whereas 3 experienced no change. All participants who completed the study rated comfort, handling, security, and discretion highly (median score 10 at baseline and at 6 weeks). CONCLUSIONS: Study findings indicate the novel ostomy barrier ring may reduce levels of peristomal MASD in persons living with an ileostomy, though a more extensive trial with a control group is recommended.